The long face and V.M.E. - Fitzpatrick Bany N. (Sciendo, 1984)
The management of the long face patient usually requires the combined efforts of both orthodontist and surgeon. Vertical maxillary excess (V.M.E.) is a type of long face problem which necessitates special understanding and will be considered in some detail.